Administrative Skills in The 21st Century of school Administrators Under Buriram Primary Educational Service Area Office 3 Based on Teacher Views: ทักษะการบริหารในศตวรรษที่ 21 ของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาบุรีรัมย์ เขต 3 ตามทัศนะของครู - Kaewuthat, Pornpimon (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2021)
The purposes of this research are 1) to study administrative skills in the 21st century of school administrators based on teacher views 2) to compare administrative skills in the 21st century of school administrators based on teacher views which classified by educational background and work experience 3) to find ways to improve administrative skills in the 21st century of school administrators under the Office of Buri Ram Primary Education Area, Area 3. The sample consisted of 331 teachers in Buri Ram Educational Service Area Office 3. The research instruments are questionnaire and interview form. There is a consistency index between 0.8 to 1.0 with confidence 0.98. The data was analyzed by using software to calculate frequency, percentage, mean and standard deviation. The research compares administrative skills in the 21st century of school administrators by using the classification of educational qualification statistics t (t-test), work experience in test statistic F( F-test) ,content analysis and summarize in essay. The results show that 1) Administrative skills in the 21st century of school administrators under Buriram Educational Service Area Office 3 based on teachers views. The overall show that, it is in the highest level. The highest mean value ​​is interpersonal skills. 2) Comparison of administrative skills in the 21st century of school administrators. Classified by educational background and work experience. The overall show that there is not different. When considering in each aspect, it is found that there are 1 aspect that has statistically significant differences at .05 levels, namely interpersonal skills. 3) Guidelines for the development of administrative skills in the 21st century of school administrators. School administrators should have a variety of management techniques. Behave to be accepted by personnel. Study information and apply ideas from the suggestions of personnel to work by making effective decisions and assign the job appropriately